Strategi Penyelenggaraan Pelayanan Perpustakaan Umum Selama Masa Pandemi Covid-19 - Budiman Muslim (THE LIGHT : Journal of Librarianship and Information Science, 2021)
In connection with the enactment of Work From Home (WFH) for employees engaged in public services, physical distancing policies, and other health procedure rules so that public services are not carried out optimally, the phenomenon of an online service system appears. Noting this phenomenon and seeing the efforts made by public service providers in dealing with this pandemic situation, library services also need to adapt by implementing an online service system. Changes or adjustments to services are a must so that the function of the library remains in demand and is useful for many people. The research was conducted qualitatively by utilizing secondary data sources obtained from official publications of agencies and institutions, applicable laws and regulations, and other related publications. Limitations in the implementation of services during the pandemic should be an opportunity for libraries to innovate. During the COVID-19 pandemic, libraries can use the following library service strategies: online public access catalog-based online search services, independent circulation services, delivery-based services, on-site reading services, user education services, collection proposal services, webinar services, information literacy services, and library and librarian consulting services.